The Role of Fraud Pentagon in Explaining Financial Reporting Fraud - Cahyaningtyas, Fadilla; Andarsari, Pipit Rosita (Rescollacom (Research Collaborations Community), 2025)
This study aims to examine the five elements of the fraud pentagon (ressure, opportunity, rationalization, capability, and arrogance) to enhance the detection and mitigation of financial statement fraud in companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. Using data from 221 firm consistently listed during the period, the study employs binary logistic regression with stata 17 to assess the influence of each elements on fraudulent financial reporting. The findings reveal that opportunity and arrogance significantly affect likelihood of financial statement fraud. Opportunity shows a positive relationship, suggesting that weak internal control and ineffective supervision increase the risk of fraudulent reporting. Conversely, arrogance exhibits a significant negative relationship, implying that grater public visibility of executives may reduce fraudulent tendencies through social mechanism. These results provide empirical support for the fraud pentagon framework and contribute to clarifying inconsistencies in previous research related to behavioral and governance factors influencing fraud. Thes study’s practical implications highlight the importance of reinforcing internal audit function, promoting ethical corporate culture, and maintaining transparency to reduce opportunities an rasionalization for fraud. Additionally, enhanced public disclosure and responsible leadership can serve as informal mechanisms to deter unethical practice. This research is limited to a three-years period and focuses on Indonesian listed firms. The measurement of arrogance using CEO photos may not fully capture to construct, and the model explains 5.46% of fraud variability, indicating the need future research that integrates qualitative methods and broader contextual factors.